IMPROVEMENT OF INVENTORY ACCOUNTING AND AUDITING IN THE FIELD OF COMMUNICATIONS - Jamilov Jushqin Jonon ugli (Research Parks Publishers, 2023)
In this article, the improvement of inventory accounting and auditing in the area of A explained. Also, the problematic aspects of inventory accounting and its determination are covered, and suggestions are made on them.